Installation Of A Supervisory Control System At A Gold Pressure-Oxidation Plant - M. Spangler (Society for Mining, Metallurgy & Exploration, 1997)
FirstMiss Gold installed a supervisory control system that is based on Pavilion Technology's Process Insights neural-network software and Oil System's PI data historian. The first successful control loop involved controlling the limestone feed rate to the neutralization circuit. The resulting improvements in the control of the circuit resulted in savings of $31,000 per month. Although it was the primary goal of the system, supervisory control of the preconditioning circuit was not achieved. However, information gained during the modeling suggested process modifications that resulted in cost savings of $54,000 per month in the preconditioning circuit.